Os significados de ter HIV em homens com diagnóstico recente: uma compreensão pela perspectiva da psicologia analítica - Rocha, Tiago André Alves da (2020)
This work comprises a qualitative study that adopted the perspective of Analytical Psychology and aimed at understanding the meanings of recent positive diagnosis of HIV/AIDS infection in men. The positive diagnosis for HIV in men has increased statistically in recent years and has revealed important psychological impacts on the individual. Although we have found research on the psychic aspects related to positive HIV diagnosis, there is a scarcity of recent studies that focus on men who have recently received a positive diagnosis. In addition, there are practically no Jungian publications relating to this theme from the framework of Analytical Psychology, a field of studies that, through a symbolic approach, can bring significant contributions to the understanding of the meanings of the diagnosis and the psychological effects and its implications for the treatment and the individuation process. Thus, we carried out a qualitative research that used, as data source, documentary records of the consultations performed at the Specialized Service (SAE) of a city in São Paulo Estate, sociodemographic questionnaire and semi-structured interviews. Participants were five male attending SAE who had received a positive HIV diagnosis in twelve months prior to the survey. The collected data were appreciated, categorized and arranged in thematic groups and themes, which, in turn, were analysed symbolically according to the concepts of Analytical Psychology. The comparison of these findings with mythological themes made it possible to broaden the understanding of symbolic meanings, which, due to their complex and multifaceted nature, can only be apprehended by approximations. The results reveal the moment of contact with the diagnosis of HIV as a milestone loaded with meanings, indicating that the knowledge of being infected promotes a crisis followed by a path of suffering, questioning and tension, with a potential for transformation. This crisis tends to lead to discoveries and adaptations. The impact reported by the participants from the contact with a positive diagnosis for HIV seems to displace the persona. The nodes, the complexes hitherto hidden come to the surface and lie bare, being associated with the meanings identified in this research: death, inferiority and isolation. Now faced with a positive diagnosis, a new reality and these meanings, the interviewees' speeches revealed negative and positive attitudes towards the external world, in terms of both facing the diagnosis and beginning antiretroviral treatment (ART). We consider that the results obtained can serve as a basis for further reflection and discussion. The conclusions from this research suggest that the symbolic approach is an important resource for the understanding of human beings in their wholeness. They also point out the responsibility of healthcare professionals in facing the symbolic marks associated with HIV and the need to create spaces for debate and problematization in favour of the articulation and complementation between the personal and the collective, among the multiple factors on the path of human development